Transferência de conhecimento e mensuração da inovação em micro e pequenas empresas do setor de transportes da cidade de Cascavel - PR - Ribeiro, Marlon Cristiano (2018)
The use of innovative practices is important for companies that seek competitiveness in the market, often this requires investment and knowledge. These difficulties can be overcome with support from knowledge-holding organizations, such a partnership can contribute to the alignment of technology transfer and knowledge. The objective of this research was to analyze the influence and effectiveness of knowledge transfer in the degree of innovation of a group of Micro and Small Enterprises (MSE) in the logistics and transportation sector of the city of Cascavel-PR. For this, a survey of longitudinal design was elaborated, in which the object of study was a group 32 MSE’s of the transport segment. It was demonstrated the degree of innovation of the MSE's in two moments, before and after a knowledge transfer shock. In order to measure the level of innovation, the tool Radar of Innovation was used, from this instrument it was possible to analyze if the process of knowledge transfer improved the nominal innovative performance of firms. To verify if the changes in the innovation indexes, post knowledge transfer, were statistically significant, analyzes of the coefficients of variation were carried out to confer the innovative cohesion of the firms and the group. The Paired Wilcoxon Test was performed to examine the hypothesis of knowledge transfer effectiveness and its influence on innovation indices. To evaluate the existence of an innovative difference between subsectors (transportation of commodities, frozen foods, parcels, dangerous cargoes, passengers and waste) the Barlett test was applied to verify if the variances of each of the groups were equal. The results show that there is an innovative behavior that is not obvious, internally the companies presented low stimulus for the approximation of sectors. Companies have been far apart in how they operate innovation. With regard to the effectiveness of the knowledge transfer, it was found that there was an influence on the innovation indices of 22 companies, although the nominal increase occurred in all of them. The same test was applied to 13 different areas, and only two were not influenced. There was no significant difference in the innovative behavior of any subgroup, indicating that no sectors are differentiated in relation to innovation or the absorption of knowledge in any area.